Increasing pleuromutilin activity of Clitopilus passeckerianus by chemical mutagenesis and improvement of production medium - Papa, Irene A.; Zulaybar, Teofila O.; Raymundo, Asuncion K. (2006)
Clitopilus passeckerianus NRRL 3100, which produces the antibiotic pleuromutilin, the precursor of the semi-synthetic Dynamutilin used solely for animal health, was mutagenized using 0.05, 0.10, 0.15, 0.20, 0.25, 0.30 and 0.35 mg mL-1 N-methyl-N'-nitro-N-nitrosoguanidine (NTG) in an attempt to increase pleuromutilin production by the organism. Percentage kills of 33.33% and 100% were obtained after an exposure to 0.05 mg mL-1 and 0.35 mg mL-1 NTG, respectively. A total of 223 colonies of C. passeckerianus, which were exposed to the mutagen NTG, showed varying antibiotic activity based on their growth inhibition of Staphylococcus aureus. Preliminary assay by the agar plug method showed that 22% mutants produced larger zones of inhibition (ZOI) than the parent strain. Using the cylinder cup method, 7% isolates produced significantly higher activity than the parent strain. Cp 76 strain mutated using 0.15 mg mL-1 NTG produced 89.36% higher yield than the parent strain. The production of pleuromutilin by the mutant Cp 76 was highest in a locally formulated medium composed of glucose, which was substituted with cassava starch, soybean meal, baker's yeast, KH2PO4, MgSO4.7H2O and CaCO3. Restricted random balance design further optimized the levels of components of the locally formulated medium to (g L-1) cassava starch, 21.0; soybean meal, 7.5; baker's yeast, 5.0; KH2PO4, 2.0 and CaCO3, 2.7. The pleuromutilin yield of mutant Cp 76 using the optimized LFM in a 2.6 L fermentor increased by 67.40% compared with the original medium composition for the production of pleuromutilin. The identity of pleromutilin was confirmed using thin layer chromatography and nuclear magnetic resonance analysis.
Keywords: Antibiotics in animal nutrition; Mutagens